Coarseness in U.S. public communication - Dalton, Philip; Kramer, Eric Mark (Fairleigh Dickinson University Press series in communication studies, 2012)
Proceeding from the assumption that all manner of public communication in the United States is becoming increasingly coarse, this book argues that shared cultural notions of decency are being eroded by market logic - a decision making calculus based solely upon the aggregate preferences of self-interested individuals. The instrumentality of communication in this paradigm eclipses communication's expressive potential, leaving our culture to value only communication's capacity to achieve individual ends.